2020
DOI: 10.4049/jimmunol.1900455
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Expansions Maintain the Clonal Stability of CD8+ T Cell Populations Undergoing Memory Inflation Driven by Murine Cytomegalovirus

Abstract: CMV is an obligate and persistent intracellular pathogen that continually drives the production of highly differentiated virus-specific CD8+ T cells in an antigen-dependent manner, a phenomenon known as memory inflation. Extensive proliferation is required to generate and maintain inflationary CD8+ T cell populations, which are counterintuitively short-lived and typically exposed to limited amounts of antigen during the chronic phase of infection. An apparent discrepancy therefore exists between the magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…We observed that public clonotypes constituted the majority of expanded clones despite accounting only for a minority of unique CDR3 sequences, which is in line with previous reports investigating this aspect for IE3- and M38-specific T cell responses at late time points of infection [ 25 ]. Beyond mere classification into private vs. public, the degree of sharedness can be highly heterogenous.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We observed that public clonotypes constituted the majority of expanded clones despite accounting only for a minority of unique CDR3 sequences, which is in line with previous reports investigating this aspect for IE3- and M38-specific T cell responses at late time points of infection [ 25 ]. Beyond mere classification into private vs. public, the degree of sharedness can be highly heterogenous.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, here we show that generation probability is a major determinant of the T cell response to SIINFEKL-expressing CMV. The results are consistent with so far described T cell responses against other natural CMV epitopes [ 25 ], arguing against a special intrinsic feature of SIINFEKL to induce (supra-)public T cell responses. Instead, the fact that similarly public responses are observed towards natural CMV epitopes points into the direction that the public nature of the T cell response could be due to the mode of antigen presentation rather than the epitope itself.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As intraplantar infection is closer to a realistic application of CMV vector-based vaccines, we focused our interest on this infection route and studied the dynamics of the CD8 T-cell response in spleen ( Figure 2) and lungs ( Figure 3) in the long-term course, monitoring a large cohort of infected mice by sampling at 3-month intervals. Recent work by Smith and colleagues [47] in a model of systemic infection after intraperitoneal virus application has shown that MI is based on the expansion of CD8 T-cell clonotypes that differ between individual mice, not by statistical error but by biological variance. Specifically, some clonotypes persisted for the entire observation period in all mice tested individually and longitudinally, although with expanding and contracting clone sizes in the time course.…”
Section: Memory Cd8 T-cell Population Dynamics Reveals Continuous Losmentioning
confidence: 99%